Analisis Performa Kualitas Air Pada Panerapan Konsep Budidaya CBIB Di Tambak Udang Pola Intensif - Abdul Wafi; Abdul Muqsith; Ach Khumaidi; Tholibah Mujtahidah (Faculty of Science and Technology University Ibrahimy, 2024)
Water quality standard criteria for shrimp farming, as regulated by the CBIB, are a crucial aspect in intensive farming operations. This research aims to assess the suitability of water quality parameters in intensive cultivation of vaname shrimp (L. vannamei) with CBIB standards (Good Fish Cultivation Methods). The research method uses an ex post facto causal design during one shrimp cultivation cycle, with a focus on the condition of water quality parameters compared with CBIB standards in accordance with Minister of Maritime Affairs and Fisheries Regulation Number 75 of 2016. The research results show that most of the water quality parameters during the cultivation period in accordance with CBIB standards, except for alkalinity and organic matter exceeding the thresholds set by CBIB. Abnormal conditions in these two parameters are caused by unpredictable natural and seasonal factors, as seen in unstable fluctuations in temperature and salinity. However, overall, the cultivation system at the research location still complies with the cultivation quality standards set by CBIB. From this discussion, it can be concluded that the water quality parameters at the research pond location are mostly in accordance with CBIB quality standards, with the exception of alkalinity and organic matter which slightly exceed the limits set by CBIB..